(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the role of the works, thoughts, and views of our great scholar, Abul-Qasim Mahmud ibn Umar ibn Muhammad az-Zamakhshari on education throughout the world and his contribution to the development of pedagogical ideas, as well as their relevance in today’s practice.